An Overview of Sky Brightness Surrounding Timau National Observatory (TNO), Indonesia - Yatini, Clara Yono; Tanesib, Jehunias L.; Maryam, Siti; Admiranto, A. Gunawan; Noor, M. Ferdhiansyah (Indonesian Journal of Geography, 2024)
This study aims to analyze skylight conditions surrounding the newly constructed Timau National Observatory (TNO) in Kupang, Indonesia. The analysis was carried out with the primary reason of determining the initial conditions and surroundings of the area, thereby providing valuable information for future observers who will be using the facility. To achieve the stated aim, the sky brightness in the study area was measured in units of magnitudes per square arcsecond (mpsas) at a 20-kilometer radius. Furthermore, numerous observations were conducted at 32 distinct observation points using Sky Quality Meter (SQM) LU-DL (SQM-LU-DL), which was directed towards the zenith. The results obtained from these observations were subsequently analyzed using Surfer software with the primary aim of determining sky brightness in the study area. The analysis showed variations in sky quality in a 20 km radius, ranging from 21.64 to 20.37 magnitudes per square arcsecond (mpsas). The measurements showed that sky quality fell between the categories of great dark and semi-suburban transitional skies. However, it was important to comprehend that recent investigations had identified bright areas surrounding the observatory area, capable of diminishing the visual quality of sky if left unaddressed.